Tools to explore ABCA3 mutations causing interstitial lung disease. Issue 12 (13th May 2016) - Wittmann, Thomas; Schindlbeck, Ulrike; Höppner, Stefanie; Kinting, Susanna; Frixel, Sabrina; Kröner, Carolin; Liebisch, Gerhard; Hegermann, Jan; Aslanidis, Charalampos; Brasch, Frank; Reu, Simone; Lasch, Peter; et al.
Summary: Background: Interstitial lung diseases (ILD) comprise disorders of mostly unknown cause. Among the few molecularly defined entities, mutations in the gene encoding the ATP‐binding cassette (ABC), subfamily A, member 3 (ABCA3) lipid transporter represent the main cause of inherited surfactant dysfunction disorders, a subgroup of ILD. Whereas many cases are reported, specific methods to functionally define such mutations are rarely presented. Materials and Methods: In this study, we exemplarily utilized a set of molecular tools to characterize the mutation K1388N, which had been identified in a patient suffering from ILD with lethal outcome. We also aimed to correlate in vitro and ex vivo findings. Results: We found that presence of the K1388N mutation did not affect protein expression, but resulted in an altered protein processing and a functional impairment of ABCA3. This was demonstrated by decreased dipalmitoyl‐phosphatidylcholine (PC 32:0) content and malformed lamellar bodies in cells transfected with the K1388N variant as compared to controls. Conclusions: Here we present a set of tools useful for categorizing different ABCA3 mutations according to their impact upon ABCA3 activity. Knowledge of the molecular defects and close correlation of in vitro and ex vivo data will allow us to define groups of mutations that can be targeted by small molecule correctors for restoring impaired ABCA3 transporter in the future.Pediatr Pulmonol. 2016;51:1284–1294. © 2016 Wiley Periodicals, Inc.